Solid Variant of Aneurysmal Bone Cyst of the Temporal Bone. (April 2018) - Saez, Neil; Sharma, Giriraj K.; Barnes, Christian H.; Lu, Yuxin; Hsu, Frank P.; Huoh, Kevin C.; Djalilian, Hamid R.; Lin, Harrison W.
Objectives: Aneurysmal bone cysts (ABC) are benign, rapidly growing osteolytic lesions. Solid variant of ABC (SVABC) is a rare subtype of ABC that has not been reported in the temporal bone. Methods: We report the case of a 6-year-old boy presenting with a slowly enlarging bony protuberance over the right zygomatic/malar eminence region. Computed tomography and magnetic resonance imaging demonstrated a 2.6 × 5.8 × 5.1 cm temporal bone mass involving the right mastoid, petrous, and temporal squamosal calvarium, with extradural intracranial extension to the middle cranial fossa. Results: The patient underwent preoperative embolization of feeder arteries followed by combined neurosurgical and neurotologic resection. Histopathology revealed characteristic ABC features with interspersed areas of intralesional osteoid formation. Conclusion: Solid variant of ABCs are rare lesions of the skull base that present a diagnostic challenge given their unique radiographic and histologic features. Thorough cytogenetic evaluation is warranted to rule out potential malignant secondary causes. Early surgical resection is essential due to the risk of intracranial extension. This is the first report of ABC of any type with concurrent involvement of the squamous, mastoid, and petrous portions of the temporal bone and the first report of SVABC of the temporal bone.